THE ROLE OF INTERNATIONAL HUMAN RESOURCE MANAGEMENT PRACTICES IN ADDRESSING JOB ALIENATION: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT ZAIN IRAQ - Sahar Jabbar Rahman (Research Parks Publishers, 2026)
This study seeks to examine the impact of international human resource management strategies on mitigating job alienation among employees in multinational corporations in Iraq. The research used a descriptive-analytical methodology and utilized a questionnaire as the primary instrument for data collection from a sample of 75 employees at Zain Iraq firms. The data were examined using the SPSS V29 software for fundamental statistical tests and the AMOS V29 software for structural equation modeling (SEM) analysis. Utilization of Structural Equation Modeling (SEM) to evaluate causal linkages among variables. International human resource management strategies include six primary dimensions: recruiting, training and development, performance assessment, compensation and incentives, leadership, and organizational communication, while job alienation is singular in nature. The findings indicated a substantial link and influence between multinational human resource practices and degrees of work alienation. Enhancing training, communication, and organizational equity mitigates feelings of alienation and fosters belonging and work satisfaction, while insufficient transparency in performance assessments and salary discrimination exacerbates isolation and detachment. The report advocates for the implementation of a national plan for international human resource management in Iraq, based on principles of justice, cultural empowerment, and the advancement of communication and collaborative training methods to foster trust and organizational loyalty.